Religiosity And Job Performance Among Muslim Self-Initiated Expatriates In Malaysia’s Service Sector: The Mediating Role Of Cross-Cultural Adjustment - Segaran, Ramya Ranee Konna (2021)
The significant aspect of the expatriation process is the expatriates’ job performance in the host country and the cross-cultural adjustment to the socio-cultural environment. Expatriates’ by and large, come from quite different socio-cultural backgrounds and different work conditions. It is interesting yet a problematic phenomenon to study their job performance and their adjustment to the new socio-cultural milieu, work environment and adoption to innovation in professional arenas. Thus, this research analyse the effect of religiosity (cognitive, affective and behavioural) and the job performance through cross-cultural adjustment (cognitive, affective and behavioural) as an mediating variable to the specific type of expatriate population – namely, on 204 Muslim Self-Initiated Expatriate (SIE) in a host country whose population is predominantly of the same religious background as the SIE. This research used a questionnaire as the method of data collection. Whereas, the analysis method used Structural Equation Modelling (SEM), SmartPLS v.3.0. The result of this research showed that the first path relationship between cognitive religiosity, affective religiosity, behavioural religiosity and job performance of SIE were significant. Next, the findings of the second path relationship indicated that there is a positive relationship between cognitive religiosity and cognitive adjustment, affective adjustment, and behavioural adjustment. Affective religiosity was found to have no relation with cross-cultural adjustment.